Pengaruh Beban Pajak, Non Debt Tax Shield, Beban Bunga, dan Pertumbuhan Aset terhadap Struktur Modal pada PT Alam - Vanny Vanny; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Ekonomis: Journal of Economics and Business, 2023)
In running a business, every company definitely needs funds to help develop its business. The funds obtained can come from the company itself or from outside parties who invest in the company. Therefore, in managing the existing funds in the company, it is necessary to have wisdom in deciding whether the funds needed within the company can then be used in accordance with the operational needs needed by the company itself. The purpose of this study was to determine and analyze the effect of Tax Expense, Non Debt Tax Shield, Interest Expense and Asset Growth on the Capital Structure. This study uses multiple linear regression analysis techniques. Data were obtained from literature related to the research topic. This can be in the form of financial statements of tax expense, non-debt tax shield, interest expense, asset growth and capital structure that affect the company. The results showed that Tax Expense has a negative effect on the Capital Structure of Alam Company, Non Debt Tax Shield has no effect on the Capital Structure of Alam company, Interest Expense has a negative effect on the Capital Structure of Alam Company, Asset Growth has a positive effect on the Capital Structure of Alam Company and the Tax Expense, Non Debt Tax Shield, Interest Expense and Asset Growth have an effect on the Capital Structure of Alam Company.